Solid-State Anaerobic Digestion of Rice Straw for Biogas Production : A Review - Shitophyta, Lukhi Mulia (Universitas Ahmad Dahlan, 2016)
AbstractBiogas is one of the alternative fuel Â to decrease the consumption of fossil fuel. Raw materials for biogas production can derive from a wide range of organic wastes including lignocellulosic biomass such as rice straw. Lignocellulosic biomass is abundant and renewable. Biogas production can be processed by solid-state anaerobic digestion. Many factors should be considered on SS-AD, including pretreatment ofÂ raw material. Therefore, the purpose of this paper is to provide existing knowledge in SS-AD, factors influencing SS-AD, pretreatment of lignocellulosic biomass and identify the preceding researches on the SS-AD.Key words: biogas, solid-state anerobic digestion, lignocellulose, rice straw